A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). VI. Fortepunctatum group - Shavrin, Alexey V. (Zootaxa, 2022)
The Fortepunctatum species group is established for two new Anthobium species from China: A. fortepunctatum sp. n. (Gansu, Shaanxi) and A. flavoguttatum sp. n. (Sichuan). The group is defined, briefly discussed, and a key to species is given. Both species are described and illustrated, and their geographical distribution is mapped.